Factors Predicting Financial Distress Retail Industry in Indonesia - Dini Iskandar; Herlina Herlina; Ida Ida; Sophia Isabella Wattimena; Benny Budiawan Tjandrasa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Indonesian retail industry has experienced significant changes during the 2020-2023 period, starting with the Covid-19 pandemic in early 2020. Although it is gradually showing signs of recovery, the companies have felt a huge impact, such as many stores closing, increasing operational costs, and decreasing consumer spending, which are challenges for retail business actors to maintain their business continuity. This study aims to determine the factors that can be predictors of the financial distress of retail industry companies in Indonesia. The sample in this study was retail industry companies listed on the Indonesia Stock Exchange for the 2019-2023 period and had complete financial reports, resulting in 10 companies. Data analysis uses the logistic regression method. The results of the study show that the debt-to-equity ratio (DER) and return on asset (ROA) have a significant effect, while the current ratio (CR), total asset turnover (TATO), and operational cash flow margin (OCF margin) do not have a significant effect on financial distress. Thus, retail industry companies can utilize debt as a financing strategy to accelerate growth and need to focus on efficient asset utilization so that they can increase revenue and profit margins in order to achieve better financial performance and reduce the risk of financial distress.